Influence Of Parenting Styles on Pupils’ Socio-Emotional Skills in Early Childhood Educational Centers in Nigeria - Olabamiji, T. O; Okewole, J. O; Gbenga-Akanmu T.O; Gbenga-Akanmu T. O., Corresponding Authour: (JECCE, 2025)
This study aims to examine the influence of parenting style on pupils’ socio-emotional skills in early childhood education centers in Nigeria. A multi-stage sampling procedure was used to select 150 parents with children in 15 early childhood education centers (ECEC) across 3 selected local government areas (LGAs) in Nigeria. This study adopted a descriptive technique and regression. Results show parenting styles exhibited by parents of pupils in ECEC as authoritative parenting styles 4.36), authoritarian parenting styles (3.39), and permissive parenting styles (3.83). Results also show a statistically significant influence of parenting styles at (β = 0.250, p = 0.002) on pupils’ socio-emotional skills in Nigeria. This study concludes that the authoritative parenting style has the highest influence on pupils’ socio-emotional skills than the other two parenting styles. This study recommends that there should be a policy that ensures better parenting styles and excellent children’s socio-emotional skills in Nigeria.